Postmodern religion (Eurasian Journal of Religious Studies, 2017)
In this article, the author examines the problem of the correlation and interrelationship betweenpostmodernism and religion, the features of postmodern religion. Religion for thousands of years fastenedthe society, united people, made their life meaningful, inhaled the meaning and animated allhuman relations. What happens to it in postmodern conditions? Does it remain a bastion of resistanceto the corrupting influence of postmodernism? It is doomed to disappear or just to metamorphize whensociety moves to its postmodern stage? The author tries to analyze the state and solution of the issue inmodernism and postmodernism, their difference.